Autophagy inhibition induced by EM-2 augments apoptosis via ROS-mediated ATM-Chk2-p53-p21 and MAPK pathway in lung and breast carcinoma - Cheng, Jinxia; Chen, Ying; Chen, Qi; Cao, Ning; He, Chuyu; Xu, Yanjun; Zhang, Xiaoying; Li, Qiang; Hong, Hong; Jiang, Jianwei; Wang, Yuechun (Frontiers in Pharmacology, 2025)
Lung cancer (LC) and breast cancer (BC) are two common malignant tumors with the highest incidence rate in men and women worldwide, respectively. As the treatment effect of currently available therapies for LC and BC is unsatisfying, searching for new therapeutic drugs has become an urgent need to be addressed. EM-2, a natural sesquiterpene lactone isolated from Elephantopus mollis H.B.K., has been previously documented to exert anti-tumor effects on liver cancer by us. However, the underlying molecular mechanisms of its resistance to LC and BC have not been clearly elucidated. Thus, in the present study, we further investigated the anticancer effect of EM-2 on LC and BC with focusing on the involved molecular mechanisms. Our results suggest that EM-2 induces the impaired autophagy, which subsequently promotes ER stress-mediated apoptosis as well as ROS generation. ROS accumulation induced by EM-2 further simultaneously induces G2/M cell cycle arrest through ATM-Chk2-p53-p21 pathway and augments cell apoptosis via MAPK-mediated signaling pathway in LC and BC cells. These results may provide the experimental basis for future clinical application of EM-2 in the treatment for LC and BC.